2020
DOI: 10.1371/journal.pgen.1009089
|View full text |Cite
|
Sign up to set email alerts
|

Automated feature extraction from population wearable device data identified novel loci associated with sleep and circadian rhythms

Abstract: Wearable devices have been increasingly used in research to provide continuous physical activity monitoring, but how to effectively extract features remains challenging for researchers. To analyze the generated actigraphy data in large-scale population studies, we developed computationally efficient methods to derive sleep and activity features through a Hidden Markov Model-based sleep/wake identification algorithm, and circadian rhythm features through a Penalized Multi-band Learning approach adapted from mac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 94 publications
2
12
0
Order By: Relevance
“…The genome-wide significant locus was found to be associated with common executive functions [39], intelligence [40], and educational attainment [41]. Furthermore, results from the single-tissue and cross-tissue transcriptome-wide association analyses further confirmed the CARE's strong biological basis and highlighted the important role of circadian rhythms on the central nervous system, which is in line with previous findings from the other UK Biobank studies [60].…”
Section: Discussionsupporting
confidence: 85%
“…The genome-wide significant locus was found to be associated with common executive functions [39], intelligence [40], and educational attainment [41]. Furthermore, results from the single-tissue and cross-tissue transcriptome-wide association analyses further confirmed the CARE's strong biological basis and highlighted the important role of circadian rhythms on the central nervous system, which is in line with previous findings from the other UK Biobank studies [60].…”
Section: Discussionsupporting
confidence: 85%
“…Hoyos et al noted marked circadian dysregulation in elderly patients with depression [ 29 ]. These psychological states can lead to reduced activity, nutritional imbalances, and other health complications, thereby fostering frailty.Lastly, CircS is closely associated with circadian rhythm disruption[ 25 , 30 ], defined as abnormalities in the biological clock’s variables over a 24-hour cycle [ 31 , 32 ]. Studies have shown that circadian rhythms are primarily regulated by the major biological clocks in the suprachiasmatic nucleus (SCN) of the hypothalamus [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The circadian rhythm is an essential cyclic oscillation system generated by the endogenous circadian clock 11,12 . Essentially all mammalian organisms have developed circadian rhythms in order to synchronize social and physiological capabilities with explicit periodicity 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…10 The circadian rhythm is an essential cyclic oscillation system generated by the endogenous circadian clock. 11,12 Essentially all mammalian organisms have developed circadian rhythms in order to synchronize social and physiological capabilities with explicit periodicity. 13,14 The control center of this circadian rhythm is located in the suprachiasmatic nucleus (SCN) of the hypothalamus, which regulates the rhythm production of various physiological functions.…”
mentioning
confidence: 99%